Reinterpretation of the third sewn boat from the ancient port of Zaton in the vicinity of ancient Nin (Aenona), Croatia - Radić Rossi, Irena; Batur, Katarina; Fabijanić, Tomislav; Romanović, Dušanka (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The port of Zaton was an ancient port of the municipium Aenona, in the province of Dalmatia. Intense port activity was recorded from the middle of the 1st until the end of the 3rd century AD. An underwater structure, either a breakwater or a pier, is visible in the maritime environment. On the inner/eastern side of this structure three sewn boats were found sunken. This paper concerns the only remaining boat at the site, Zaton 3, discovered in 2002 and recently reinvestigated. The paper presents the hull construction features.